Asia Tenggara: Kawasan yang Tengah Berkembang - Emil Radhiansyah (Budapest International Research and Critics University, 2016)
This article is intended to analize the development of South East Asia countries. South East Asia is a region with continuous development, both its politic and economic. The next development of South East Asia lies in its society. With its regional organization, ASEAN, South East Asia has a great opportunity to play its significantroles in international community. The unity and cooperation among South East Asia countries is certainly stronger since the ASEAN Community will come into effect in 2015 through some pillars: politic and security, economy and socio-culture.